A new polymorph of NH4V3O7: Synthesis, structure, magnetic and electrochemical properties - Zakharova, Galina S.; Ottmann, Alexander; Ehrstein, B.; Tyutyunnik, A. P.; Zhu, Q.; Lu, S.; Voronin, V. I.; Enyashin, A. N.; Klingeler, Rüdiger (Solid state sciences, 2016)
NH4V3O7 micro-sized crystals have been successfully synthesized via a conventional hydrothermal synthesis route. The products were characterized by means of X-ray and neutron powder diffraction, scanning electron microscopy, transmission electron microscopy, Fourier transform infrared spectroscopy, static magnetization measurements, and electrochemical cycling. The diffraction patterns of NH4V3O7 can be indexed in the monoclinic space group P21 with the cell parameters a = 12.247(5) Å, b = 3.4233(10) Å, c = 13.899(4) Å, β = 87.72(3)°, and V = 582.3(4) Å3. The crystal structure is built up of (V3O7)-layers with V4+-and V5+-ions, which occupy oxygen octahedra and tetrahedra, respectively. The (V3O7)-layers are bonded by (NH4)+ -ions. Analysis of the magnetization data confirms that 2/3 of the V-ions are 4 + associated with S = 1/2. Roughly half of them are strongly coupled to antiferromagnetic dimers (J = 720 K), the other half is only weakly (J of several 10 K) antiferromagnetically interacting. Electrochemical cycling shows reversible lithium de-/intercalation into the layered NH4V3O7 host structure with an initial specific discharge capacity of 310 mAh/g at 7 mA/g.